Phenotypic Changes and Impaired Function of Peripheral γδ T Cells in Patients With Sepsis. Issue 3 (September 2017) - Liao, Xue-Lian; Feng, Ting; Zhang, Jiang-Qian; Cao, Xing; Wu, Qi-Hong; Xie, Zhi-Chao; Kang, Yan; Li, Hong
ABSTRACT: Introduction: Recent studies demonstrated the significant loss of gamma delta T (γδ T) cells in patients with sepsis. Given the distinct functions of γδ T cells in human anti-infection immunity, we are interested in evaluating the phenotype and function of peripheral γδ T cells in septic patients and determining their prognostic implication. Method: This prospective study has been conducted in three intensive care units of a university hospital. During the period from October 2014 to June 2015, we enrolled 107 patients who were consecutively admitted and diagnosed with severe sepsis or septic shock (excluding previous immunosuppression) and 45 healthy controls. Using flow cytometry, we analyzed the in vivo percentage of γδ T cells in cluster of differentiation (CD)3 + cells from peripheral blood mononuclear cells as well as their expression of surface markers (CD69, natural-killer group 2 member D [NKG2D], programmed death receptor 1 [PD-1]) and intracellular cytokines (interferon-γ [IFN-γ], interleukin [IL]-17, IL-10, transforming growth factor-β [TGF-β]). Then we further evaluated the different responses of γδ T cells after the antigen stimulation ex vivo by measuring CD69 and IFN-γ expression. Lastly, we conducted the multiple logistic regressions to analyze the risk factor for prognosis. Results: Compared with control group, γδ T cells in septic patients displayed a decrease in percentage, increase in CD69, decrease in NKG2D, and increase in cytokine expression (pro-inflammatory IFN-γ, IL-17, anti-inflammatory IL-10, TGF-β) in vivo . After the antigen stimulation ex vivo, both CD69 and IFN-γ expression in γδ T cells were significantly lower in septic patients than control group. Importantly, the decrease in CD69 and IFN-γ expression was more pronounced in non-survivors than survivors. Multiple logistic regression analysis revealed that lower expression of IFN-γ after stimulation is a dependent risk factor that associated with patient 28-day death in septic patients (OR: 0.908 [95% CI: 0.853–0.966]). Conclusion: Septic patients showed altered phenotype and function of γδ T cells. The impaired IFN-γ expression by γδ T cells after the antigen stimulation is associated with mortality in septic patients. Abstract : Supplemental Digital Content is available in the text